Mobile augmented reality in electronic commerce: investigating user perception and purchase intent amongst educated young adults - Haile, Tegegne Tesfaye; Kang, Mincheol (Sustainability (Switzerland), 2020)
Even though the presence and use of mobile augmented reality (MAR) technology has become increasingly popular in the field of marketing and advertising in recent years, it has largely been neglected in the study of consumer behavior research. This paper utilizes a single-group posttest-only quasi-experimental design to investigate how the feature of mobile augmented reality application influences consumers’ attitude and purchasing intention as explained by the dimensions of persuasion (i.e., consumers’ cognitive, affective, and conative dimensions). Structural Equation Modeling (SEM) with SPSS and AMOS is used to analyze the psychometric survey data collected from 179 participants. The results supported the prediction that MAR application’s real-time interactivity and entertainment increase cognition and affection, respectively; while irritation with MAR application decreases affection. The unsupported hypothesis, which predicted a positive relationship between informativeness and cognition, came as a surprise. The overall result of the study demonstrates the positive influence of MAR application in enhancing consumers’ purchasing intention. Finally, implications and future research directions are discussed.
Keywords: Dimensions of persuasion; MAR; Mobile augmented reality; Purchasing intention